Students’ Perceptions of Teachers’ Corrective Feedback, Basic Psychological Needs and Subjective Vitality: A Multilevel Approach - Vergara-Torres, Argenis P.; Tristán, José; López-Walle, Jeanette M.; González-Gallegos, Alejandra; Pappous, Athanasios (Sakis); Tomás, Inés (Frontiers in Psychology, 2020)
The way students perceive corrective feedback has repercussions on what they learn and think. Based on the self-determination theory, the aim of this study is to test a model of multilevel mediation that examines the relationships between the perception of corrective feedback with its degree of acceptance (perceived legitimacy) at the team level and the subjective vitality of students at the individual level, mediated by the satisfaction of the three psychological needs, in the context of physical education. The participants were 742 students aged between 10 and 13 years old (52.6% men, 47.4% women) in 29 physical education groups. The results of the multilevel structural equation modeling analysis found at the group (between) level a positive and significant relationship between corrective feedback and perceived legitimacy (Bbetween = 0.49, p < 0.01), as well as a positive and significant relationship between perceived legitimacy and the needs of competence (Bbetween = 0.66, p < 0.05) and relatedness (Bbetween = 0.95, p < 0.01). In addition, there was a positive and significant association between competence and subjective vitality (Bbetween = 2.06, p < 0.01), and a negative and significant association between relatedness and subjective vitality (Bbetween = −0.85, p < 0.01). Also, on an individual (within) level, the needs of autonomy (Bwithin = 0.09, p < 0.05), competence (Bwithin = 0.27, p < 0.01), and relatedness (Bwithin = 0.17, p < 0.01) were positively and significantly associated with subjective vitality. Finally, corrective feedback showed a positive indirect effect on subjective vitality through perceived legitimacy and competence, while the indirect effect was negative through perceived legitimacy and relatedness. In conclusion, on an individual level, students who perceive their basic psychological needs to be met in turn, increase their subjective vitality. At the group level, the results are discussed. These findings suggest that teachers might be best advised to ensure that their students accept corrective feedback, by having it couched in a manner that suggests that learning and improvement can follow, and communicated in an autonomy-supporting way.